AC electrical characterisation and insight to charge transfer mechanisms in DNA molecular wires through temperature and UV effects. Issue 3 (1st June 2015) - Kassegne, Sam; Wibowo, Denni; Chi, James; Ramesh, Varsha; Narenji, Alaleh; Khosla, Ajit; Mokili, John
Abstract : In this study, AC characterisation of DNA molecular wires, effects of frequency, temperature and UV irradiation on their conductivity is presented. λ‐DNA molecular wires suspended between high aspect‐ratio electrodes exhibit highly frequency‐dependent conductivity that approaches metal‐like behaviour at high frequencies (∼MHz). Detailed temperature dependence experiments were performed that traced the impedance response of λ‐DNA until its denaturation. UV irradiation experiments where conductivity was lost at higher and longer UV exposures helped to establish that it is indeed λ‐DNA molecular wires that generate conductivity. The subsequent renaturation of λ‐DNA resulted in the recovery of current conduction, providing yet another proof of the conducting DNA molecular wire bridge. The temperature results also revealed hysteretic and bi‐modal impedance responses that could make DNA a candidate for nanoelectronics components like thermal transistors and switches. Further, these experiments shed light on the charge transfer mechanism in DNA. At higher temperatures, the expected increase in thermal‐induced charge hopping may account for the decrease in impedance supporting the 'charge hopping mechanism' theory. UV light, on the other hand, causes damage to GC base‐pairs and phosphate groups reducing the path available both for hopping and short‐range tunneling mechanisms, and hence increasing impedance – this again supporting both the 'charge hopping' and 'tunneling' mechanism theories.